STUDENT’S READINESS TO CARRY OUT FACE-TO-FACE LEARNING AT KENDARI VOCATIONAL HIGH SCHOOL - Hengki Satrianta; Darmawansyah; Linda Kahar (Paedagogia: Jurnal Pendidikan, 2022)
The slowing spread of Covid-19 infections has brought positive changes in the education sector. The issue of implementing limited face to face learning begins to excite students in gaining knowledge. Online learning effects for approximately two years was relatively difficult to keep students away from themselves. This study time to determine how the level of student learning readiness in facing offline learning. This was quantitative research with a survey type. The population were State vocatoonal high school 2 Kendari students, totaling 558 students. The sample was drawn randomly with a magnitude estimated using the Slovin formula at a significance of 5% so that the total sample size was 233 students. Data were collected by learning readiness scale. Data were analyzed descriptively and comparative statistics. The results showed that the learning readiness of State vocatoonal high school Negeri 2 Kendari students was in the high category and female students had a higher level of learning readiness than male students.